The Effect of Buy and Sell Financing (Murabahah), Profit Share Financing (Mudarabah), Equity Capital Financing (Musyarakah) and Non-Performing Financing Ratio on Profitability Level of Sharia Commercial Banks in North Sumatera - Daniel Yusuf; Hamdani; Kholilul Kholik (Britain International for Academic Research (BIAR) Publisher, 2019)
The aim of this study is to determine the effect of buy and sell financing (murabahah), profit share financing (mudarabah), equity capital financing (musyarakah) and non-performing financing (NPF) ratio as a whole (Simultaneous) on profitability level of Sharia Commercial Banks in North Sumatera. The population of the study are all Sharia Commercial Banks in North Sumatera which amounted to 6 banks. The population in this study is the annual financial reports regarding Islamic banking which taken from the financial reports of each banks for the period 2011-2015. The sample is done by nonrandom (nonprobability sampling) with purposive sampling method which is done by taking samples from the population based on certain criteria. Based on the results of secondary data processing with data analysis technique used is multiple regression analysis and classical assumption (normality test, heterokedastisitas, multikoliniearitas, autocorrelation and also significance test (t test, F test, the coefficient of determination). It is known that buy and sell financing (murabahah), profit share financing (mudarabah), equity capital financing (musyarakah) and non-performing financing (NPF) ratio simultaneously has a significant effect on ROA.